Variability in Greenhouse Gas Emissions from Permafrost Thaw Ponds - Laurion, Isabelle; Vincent, Warwick F.; MacIntyre, Sally; Retamal, Leira; Dupont, Christiane; Francus, Pierre; Pienitz, Reinhard (Limnology and oceanography, 2010)
Arctic climate change is leading to accelerated melting of permafrost and the mobilization of soil organic carbon pools that have accumulated over thousands of years. Photochemical and microbial transformation will liberate a fraction of this carbon to the atmosphere in the form of CO₂ and CH₄. We quantified these fluxes in a series of permafrost thaw ponds in the Canadian Subarctic and Arctic and further investigated how optical properties of the carbon pool, the type of microbial assemblages, and light and mixing regimes influenced the rate of gas release. Most ponds were supersaturated in CO₂ and all of them in CH₄. Gas fluxes as estimated from dissolved gas concentrations using a wind-based model varied from -20.5 to 114.4 mmol CO₂ m⁻² d⁻¹, with negative fluxes recorded in arctic ponds colonized by benthic microbial mats, and from 0.03 to 5.62 mmol CH₄ m⁻² d⁻¹. From a time series set of measurements in a subarctic pond over 8 d, calculated gas fluxes were on average 40% higher when using a newly derived equation for the gas transfer coefficient developed from eddy covariance measurements. The daily variation in gas fluxes was highly dependent on mixed layer dynamics. At the seasonal timescale, persistent thermal stratification and gas buildup at depth indicated that autumnal overturn is a critically important period for greenhouse gas emissions from subarctic ponds. These results underscore the increasingly important contribution of permafrost thaw ponds to greenhouse gas emissions and the need to account for local and regional variability in their limnological properties for global estimates.